Multi-Wavelength Photoplethysmography Device for Measuring Cardiovascular and Haemodynamic Parameters : Design and Implementation - Sirkiä, Jukka-Pekka (My University, 2020)
Cardiovascular diseases cause the most deaths globally, approximately one third of all deaths. The leading risk factor for cardiovascular diseases is hypertension which usually does not have any visible symptoms, and hence can only be detected by measurement. In this thesis a multi-wavelength photoplethysmography device able to measure pulse transit time in the skin microvasculature (PTTM) together with more typical parameters, such as heart rate and blood oxygen saturation, is developed. The long-term goal, which is outside the scope of this thesis, is to relate PTTM to blood pressure, creating a new convenient way to measure blood pressure. The developed device is a prototype experimenting on measuring PTTM and investigating possible areas of improvement in the challenging goal. The developed device is able to make simultaneous measurements at five different wavelengths (465 nm, 515 nm, 590 nm, 640 nm and 880 nm) with a maximum sampling rate of 625 Hz per channel. The wavelengths were selected based on the theory of light-skin interaction so that all important depths of the skin – papillary and reticular sublayers of dermis together with the junction of the reticular layer and the underlying hypodermis – can be reached. The design of the device is explained from all relevant perspectives, from the design of the printed circuit boards and mechanical design to programming the device firmware and the accompanying computer software. The level of details is kept high to provide as clear view as possible to the design process. The device was successfully implemented and then verified by measuring voltages from critical parts of the circuits. In addition, test measurements were performed to estimate the capability of the device. The measurement results showed that the device produces high quality signal from which it is possible to compute the small PTTM values. Moreover, with the help of Valsalva maneuver (which causes sudden changes both in heart rate and blood pressure), the relation between PTTM and blood pressure was shown. Some improvement suggestions are also presented together with a direction for future research. The developed device worked also as a basis for an article prepared for the Computing in Cardiology conference held in Italy in September 2020.

Sydän- ja verisuonitaudit aiheuttavat maailmanlaajuisesti noin joka kolmannen kuoleman, mikä tekee niistä yleisimmän kuolinsyyn. Suurin yksittäinen riskitekijä sydän- ja verisuonitaudeille on kohonnut verenpaine, joka harvoin aiheuttaa havaittavia oireita. Verenpaineen mittaaminen onkin ainoa tapa todentaa riskitekijän olemassaolo. Tässä diplomityössä esitellään moniaallonpituusfotopletysmografiaan perustuva laite, joka kykenee paitsi mittaamaan pulssin kulkuaikaa ihonalaisessa mikroverisuonistossa (PTTM), myös tavallisempia paremetreja kuten sydämen sykettä ja veren happipitoisuutta. Pitkän aikavälin tavoitteena on löytää selkeä yhteys PTTM:n ja verenpaineen välillä, mikä mahdollistaisi uudenlaisen tavan mitata verenpainetta. Kehitetyn laitteen perimmäinen tarkoitus onkin toimia prototyyppinä PTTM-arvojen mittaamisessa ja menetelmän kehittämisessä. Kehitetty laite pystyy tekemään samanaikaisia mittauksia viidellä eri valon aallonpituudella (465 nm, 515 nm, 590 nm, 640 nm ja 880 nm) näytteenottotaajuuden ollessa enintään 625 Hz kanavaa kohden. Käytettävät aallonpituudet valittiin valon ja ihon vuorovaikutusteorian perusteella siten, että pulssia voidaan mitata eri kohdista verinahkaa aina nystykerroksesta verkkokerroksen ja ihonalaiskerroksen rajapintaan asti. Laitteen suunnittelu selitetään monesta eri näkökulmasta sisältäen piirilevyjen ja mekaanisen suunnittelun kuin myös laitteen ja sen vaatiman ohjelmiston ohjelmoinnin. Mahdollisimman selkeän kuvan antamiseksi työssä on pyritty selittämään asiat hyvinkin seikkaperäisesti. Laite toteutettiin onnistuneesti ja sen toiminta varmistettiin mittaamalla jännitteitä laitteen virtapiireistä. Tämän lisäksi laitteella tehtiin mittauksia sen kliinisen toiminnan arvioimiseksi. Mittaustulokset osoittivat, että laite tuottaa korkealaatuista signaalia, josta voidaan laskea arvoiltaan pieniä PTTM-arvoja. PTTM-arvojen ja verenpaineen välistä yhteyttä havainnollistettiin Valsalva-menetelmän avulla, joka aiheuttaa äkillisiä muutoksia sydämen sykkeessä ja verenpaineessa. Työn lopuksi tuodaan esille parannusehdotuksia ja esitetään suunta jatkotutkimukselle. Kehitetyn laitteen pohjalta kirjoitettiin myös artikkeli Computing in Cardiology -konferenssiin, joka pidettiin syyskuussa 2020.
Keywords: Photoplethysmography, pulse transit time, microvasculature.